Optimal Reserves in the Eastern Caribbean Currency Union - Samuel, Wendell (IMF Working Papers; Working Paper, 2009)
Recent turbulence in global and Caribbean regional financial markets underscore the importance of reassessing the adequacy of international reserves held by the Eastern Caribbean Central Bank (ECCB). Using the Jeanne (2007) optimization framework, this paper finds that international reserves held by the ECCB are generally adequate for a variety of external current account and capital account shocks. However, the ECCB would be challenged in the event of moderate to severe deposit outflows.